2022
DOI: 10.3390/ijms231810729
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis and Fecal Microbiota Transplantation in Autoimmune Diseases

Abstract: Gut microbiota dysbiosis has recently been reported in a number of clinical states, including neurological, psychiatric, cardiovascular, metabolic and autoimmune disorders. Yet, it is not completely understood how colonizing microorganisms are implicated in their pathophysiology and molecular pathways. There are a number of suggested mechanisms of how gut microbiota dysbiosis triggers or sustains extraintestinal diseases; however, none of these have been widely accepted as part of the disease pathogenesis. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 124 publications
1
22
0
Order By: Relevance
“…Gastrointestinal microbiota dysbiosis can contribute to autoimmune disorders [ 35 , 75 , 76 ]. Probiotics not only reshape the host microbiota but also impact global metabolic functions, offering potential autoimmune disorder treatments [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal microbiota dysbiosis can contribute to autoimmune disorders [ 35 , 75 , 76 ]. Probiotics not only reshape the host microbiota but also impact global metabolic functions, offering potential autoimmune disorder treatments [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of the ocular surface microbiome in oGVHD are unknown, there is increasing evidence that gut dysbiosis can lead to autoimmune disease. 62 Using 16S ribosomal RNA gene sequencing, De Paiva et al 63 also found a diverse mucosal microbiome in patients with severe SS. However, unlike oGVHD, a time zero cannot be established in SS.…”
Section: Time Zero: a Chronicle Of Immune Infiltrationmentioning
confidence: 99%
“…Oral bacterial liquid capsules and nasal feeding tubes have primarily been used ( Green et al., 2020 ; Allegretti et al., 2021 ), and donor sources include autologous and allogeneic floral transplantations. In clinical studies on FMT in patients with diabetes ( Aron-Wisnewsky et al., 2019 ; Belvoncikova et al., 2022 ; Hou et al., 2022 ; Zhang et al., 2022 ), a healthy human fecal donor who meets the relevant requirements is most commonly selected. When traditional hypoglycemic drugs are ineffective or cannot be tolerated, FMT, as a way to intervene in the gut microbiota, has a satisfactory overall effect with advantages such as high clinical safety and few adverse reactions ( Wang et al., 2022a ).…”
Section: Gut Microbiota and Dmmentioning
confidence: 99%